Interactive digital tools to support empowerment of people with cancer : a systematic literature review - Tuominen, Leena; Leino-Kilpi, Helena; Poraharju, Jeena; Cabutto, Daniela; Carrion, Carme; Lehtiö, Leeni; Moretó, Sónia; Stolt, Minna; Sulosaari, Virpi; Virtanen, Heli (Springer Nature, 2025)
Purpose: To identify and synthesise interactive digital tools used to support the empowerment of people with cancer and the outcomes of these tools.
Methods: A systematic literature review was conducted using PubMed, CINAHL, Web of Science, Cochrane, Eric, Scopus, and PsycINFO databases in May 2023. Inclusion criteria were patient empowerment as an outcome supported by interactive digital tools expressed in study goal, methods or results, peer-reviewed studies published since 2010 in cancer care. Narrative synthesis was applied, and the quality of the studies was assessed following Joanna Briggs Institute checklists.
Results: Out of 1571 records screened, 39 studies published in 2011-2022 with RCT (17), single-arm trial (15), quasi-experimental (1), and qualitative designs (6) were included. A total of 30 interactive digital tools were identified to support empowerment (4) and related aspects, such as self-management (2), coping (4), patient activation (9), and self-efficacy (19). Significant positive effects were found on empowerment (1), self-management (1), coping (1), patient activation (2), and self-efficacy (10). Patient experiences were positive. Interactivity occurred with the tool itself (22), peers (7), or nurses (7), physicians (2), psychologists, (2) or social workers (1).
Conclusion: Interactive digital tools have been developed extensively in recent years, varying in terms of content and methodology, favouring feasibility and pilot designs. In all of the tools, people with cancer are either active or recipients of information. The research evidence indicates positive outcomes for patient empowerment through interactive digital tools. Thus, even though promising, there still is need for further testing of the tools.